Screening of biomass production of cultivated forage grasses in response to mycorrhizal symbiosis under nutritional deficit conditions - Cavagnaro, Romina Andrea (2014)
Arbuscular mycorrhizal fungi (AMF) colonize the root systems of most natural grassland species and usually increase plant growth by enhancing nutrients provision. This effect on growth responses of cultivated forage grasses is scarcely known, particularly under nutritional deficit conditions. We examined total biomass production, aboveground and belowground biomass and tillering of three temperate and three tropical cultivated forage grasses. Seedlings of each species were inoculated with a mixture of mycorrhizal fungi and later grown for 5 months under nutritional deficit conditions. The mycorrhizal symbiosis promoted aboveground and belowground biomass production in five out of six grass species. Grass species differed in their mycorrhizal responsiveness: tropical grasses (Panicum coloratum cv. Klein = Brachiaria brizantha cv. Marandú > Paspalum dilatatum cv. Primo) responded better than temperate (Festuca arundinacea cv. Royal > Agropyron elongatum cv. Hulk), while the temperate Dactylis glomerata cv. Porto did not respond to AMF inoculation. In four of the species, the changes observed in aboveground biomass were explained by the total number of tillers, while, in P. dilatatum, changes were accounted for by the individual weight of mature tillers. On the whole, the screening of cultivated forage grasses revealed that tropical grasses were highly responsive to mycorrhizae, in contrast to a lower effect on the growth of temperate grasses.